Assessment of nurses’ familiarity with the principles of aseptics and antiseptics in selected medical procedures - Kosonóg, Katarzyna; Gotlib, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Preventing infections among patients is possible thanks to the application of the achievements of aseptics and antiseptics. Familiarity with the principles of application of aseptic and antiseptics is of major importance for nurses. Aim of the study. The aim of this paper is to provide a preliminary assessment of nurses’ familiarity with the principles of aseptics and antiseptics, their application in selected medical procedures and to identify the relation between the level of knowledge and the type of work place. Material and methods. One hundred nurses employed at primary care facilities in Warsaw and smaller towns and at surgical departments in Warsaw hospitals. An anonymous questionnaire designed by the authors (20 closed single-choice questions) was distributed in March 2009. The results were compared using descriptive statistics. Results. Eighty six percent of the respondents identified aseptics as procedures aiming to protect naturally sterile tissues from contamination during invasive procedures; 64% of the respondents pointed to iodine compounds and quaternary ammonia bases as the compounds recommended for disinfecting the skin before invasive procedures; 55% of the respondents wrote that iodophors have bactericidal, viricidal and fungicidal effects. According to the respondents, hands are the most important vector for transmission of infection in the hospital; 60% of the respondents knew that the Ayliffe technique is a hand-washing technique. Conclusions: 1. Nurses’ familiarity with aseptic and antiseptic principles in selected medical procedures is varied and insufficient. 2. The best results were obtained by nurses working in hospitals, which may be related to the fact that more than half of this group had a university degree. 3. The level of familiarity among nurses working at primary care facilities does not depend on the size of the town. 4. Training should be offered to improve nurses’ familiarity with aseptics and antiseptics. Nursing Topics 2010; 18 (1): 30-40